Genomic profile in association with sport-type, sex, ethnicity, psychological traits and sport injuries of elite athletes - Silva, H. H.; Silva, M. G.; Cerqueira, F.; Tavares, V.; Medeiros, R. (The Journal of Sports Medicine and Physical Fitness, 2022)
In the last few years, some inherited determinants have been associated with elite athletic performance, but its polygenic trait character has limited the correct definition of elite athlete`s genomic profile. This qualitative descriptive study aims to summarize the current understanding about genetic and epigenetic factors in elite athletes, as well as their genomic profile in association with sport-type, sex, ethnicity, psychological traits and sport injuries. A narrative review of the literature across a broad cross-section of the elite athletes` genomic profile was undertaken. Elite performance relies on rare gene variants within a great interface between molecular, cellular and behavioral sport-related phenotypes and the environment, which is still poorly understood. ACTN3 rs1815739 and ACE I/D polymorphisms appear to be associated to specific sprint phenotypes and influence the athletic status, i.e., the rs1815739 variant is more influential to 200-m performance and the ACE ID polymorphism is more involved in the longer, 400-m sprint performance. Generally, athletes show endurance-based sports characteristics or power-based sports characteristics, but some studies have reported some genes associations to both sports-based characteristics. Furthermore, genetic studies with larger cohorts of single-sport athletes might be preferable than studies combining athletes of different sports, given the existence of distinct athlete profiles and sport demands. Athletic performance may be influenced by the serotonergic pathway and the potential injury risk (namely stress fracture) might be associated to a genetic predisposition associated to the mechanical loading from the intense physical exercise. The study of gene variants associated to sex and ethnicity-related to athletic performance needs further investigation. The combination of genome-wide association studies addressing the genetic architecture of athletes and the subsequent replication and validation studies might for additional genetic data is mandatory.